PENGARUH KONSENTRASI EKSTRAK DAUN KEMANGI (Ocimum sanctum) UNTUK PENGENDALIAN AKAR GADA (Plasmodiophora brassicae) PADA TANAMAN CAISIM (Brassica juncea L.) - Jefri Sasongko; Anis Shofiyani; Oetami Dwi Hajoeningtijas (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2016)
People demand on Caisim (Brassicaejuncea L.) is progressively increasing. One of offorts that can be applied for increasing Caisim crop is by fertilization. Clup root disease caused by Plasmodiophorabrassicae fungi is the most important fungal plant disease infecting cabbagecrop types. This pathogenic fungal infection causes crop damage until 100% or crop failure. One of the disease integeated controlling components that can be developed is biological control. One of biological pesticides for controlling this fungal plant disease is Basil plant.This research aimed to observe effect of the best basil concentration extract for club root control. It was conducted in Laboratory of UniversitasMuhammadiyahPurwokerto and Dukuwaluh Village, Kembaran Sub-district. The research period was three (3) months : Juneto September 2016. The researcher used Random Group Design (RAK). The tested factor including only one factor. K0: control, K1: 50 g/l, K2 : 100 g/l, K3 : 150 g/l, K4 : 200 g/l. the effect of Bassil extract on K1 concrentation resulted the disease with the highest score0.75%, K2 concentration resulted the disease whit the highest disease index 1.17, K4 concentration resulted the tallest plant height 10.1 cm and K3 concentration resulted the heaviest wotwoight 12.2 g.